FAKTOR KOMUNIKASI DAN KETERSEDIAAN SUMBER DAYA DALAM IMPLEMENTASI KONSELING AIR SUSU IBU OLEH BIDAN KONSELOR ASI - Mina Yumei Santi; Ani Margawati; Atik Mawarni (Kesmas Indonesia, 2015)
The exclusive breastfeeding coverage in Bantul district in 2011 was the third lowest in Yogyakarta Province is 42.34%, otherwise Bantul is a district that has the highest number of midwives counselor of breastfeeding with 40 persons. The aim of this research was to analyze the communication factor and the availability of resources in the implementation of exclusive breastfeeding counseling by midwives counselor of breastfeeding at Public Health Centers in Bantul. This was descriptive qualitative research using a purposive sampling. The main informant are 4 midwives counselor of breastfeeding in health centers and triangulation informants namely 4 head of health centers, 4 coordinator of midwives, 1 head of nutrition section and 12 mothers i.e. pregnant women, postpartum mothers and mothers of infants that are immunized at health center. Data were collected from in-depth interview and observation. Processing and analysis of data by using content analysis. The result of this research shows that breastfeeding counseling by midwives counselor of breastfeeding has not done well, socialization efforts not optimally, lack of human resources and inadequate support facilities. It is suggested to Bantul Regency Health Office to make efforts to socialization; improve resource procurement efforts; formulate specific main tasks and functions of midwife counselor of breastfeeding. The health centers to allocate funds for breasfeeding counseling.